HDAC Inhibition Reverses Preexisting Diastolic Dysfunction and Blocks Covert Extracellular Matrix Remodeling. Issue 19 (11th May 2021) - Travers, Joshua G.; Wennersten, Sara A.; Peña, Brisa; Bagchi, Rushita A.; Smith, Harrison E.; Hirsch, Rachel A.; Vanderlinden, Lauren A.; Lin, Ying-Hsi; Dobrinskikh, Evgenia; Demos-Davies, Kimberly M.; Cavasin, Maria A.; Mestroni, Luisa; et al.
Abstract : Background: Diastolic dysfunction (DD) is associated with the development of heart failure and contributes to the pathogenesis of other cardiac maladies, including atrial fibrillation. Inhibition of histone deacetylases (HDACs) has been shown to prevent DD by enhancing myofibril relaxation. We addressed the therapeutic potential of HDAC inhibition in a model of established DD with preserved ejection fraction. Methods: Four weeks after uninephrectomy and implantation with deoxycorticosterone acetate pellets, when DD was clearly evident, 1 cohort of mice was administered the clinical-stage HDAC inhibitor ITF2357/Givinostat. Echocardiography, blood pressure measurements, and end point invasive hemodynamic analyses were performed. Myofibril mechanics and intact cardiomyocyte relaxation were assessed ex vivo. Cardiac fibrosis was evaluated by picrosirius red staining and second harmonic generation microscopy of left ventricle (LV) sections, RNA sequencing of LV mRNA, mass spectrometry–based evaluation of decellularized LV biopsies, and atomic force microscopy determination of LV stiffness. Mechanistic studies were performed with primary rat and human cardiac fibroblasts. Results: HDAC inhibition normalized DD without lowering blood pressure in this model of systemic hypertension. In contrast to previous models, myofibril relaxation was unimpaired in uninephrectomy/deoxycorticosterone acetate mice. Furthermore, cardiac fibrosis was not evident in any mouse cohort on the basis of picrosirius red staining or second harmonic generation microscopy. However, mass spectrometry revealed induction in the expression of >100 extracellular matrix proteins in LVs of uninephrectomy/deoxycorticosterone acetate mice, which correlated with profound tissue stiffening based on atomic force microscopy. ITF2357/Givinostat treatment blocked extracellular matrix expansion and LV stiffening. The HDAC inhibitor was subsequently shown to suppress cardiac fibroblast activation, at least in part, by blunting recruitment of the profibrotic chromatin reader protein BRD4 (bromodomain-containing protein 4) to key gene regulatory elements. Conclusions: These findings demonstrate the potential of HDAC inhibition as a therapeutic intervention to reverse existing DD and establish blockade of extracellular matrix remodeling as a second mechanism by which HDAC inhibitors improve ventricular filling. Our data reveal the existence of pathophysiologically relevant covert or hidden cardiac fibrosis that is below the limit of detection of histochemical stains such as picrosirius red, highlighting the need to evaluate fibrosis of the heart using diverse methodologies. Abstract : Supplemental Digital Content is available in the text.